Pengaruh Work Life Balance dan Disiplin Kerja Terhadap Produktivitas Karyawan Seblak Bageur Bandung - Mia Istiqomah; Hangga Novian (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the influence of Work Life Balance and Work Discipline on Employee Productivity at Seblak Bageur Bandung. The research background is based on operational phenomena such as high work intensity, consumer complaints regarding service accuracy, and pre-survey results indicating that Work Life Balance and Work Discipline are dominant factors affecting productivity. This study uses a quantitative method with descriptive and verificative approaches. The research population consisted of 34 employees, all of whom were used as samples through total sampling technique. Instruments in the form of questionnaires were tested for validity and reliability, then analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results show that: (1) Partially, Work Life Balance (X1) has a regression coefficient of 0.801 > 0.3388, so H1 is accepted; Work Discipline (X2) has a regression coefficient of 0.862 > 0.3388, so H2 is accepted. (2) Simultaneously, Work Life Balance does not have a significant effect on productivity because the Work Discipline variable is more dominant, with a regression coefficient (b1) of 0.125, t-value of 0.591, and significance of 0.559. Meanwhile, Work Discipline has a stronger influence with a regression coefficient (b2) of 0.749, t-value of 3.543, and significance of 0.001. Overall, this study confirms that improving Work Life Balance and especially Work Discipline is an important strategy for increasing employee productivity at Seblak Bageur Bandung.